Deepening apartheid: The political geography of colonizing Israel/Palestine - Yiftachel, Oren (Frontiers in Political Science, 2023)
The paper analyzes the regime in Israel/Palestine using a political geographical perspective. It demonstrates how a combination of colonial, national, capitalist and capitalist forces have put in train a process of 'deepening apartheid' in the entire territory between River and Sea. This undeclared de facto regime has been established to guard the 'achievements' of settler colonial Judaization of the land and the domination of the Jewish minority. As described by the Rome Statute, it has become an institutionalized regime of systematic oppression and domination by one group over others, with the intention of maintaining that regime. Hence the political geographical analysis shows clearly that the wide description in academic and international circles of Israel as 'Jewish and democratic', is based on a denial of the spatial, violent, legal and political processes that stratify the population into a clear racialized hierarchy of civil statuses.. Theoretically, the paper draws on the links between settler colonial expansion, the rise of ethnocracy, partial liberalization under global capitalism, and the making of apartheid. It shows that historically Jewish colonization of Palestine – the underlying logic of the regime -- has advanced in six main historical-geographical stages, encountering persistent, and at times violent, Palestinian resistance. The paper analyzes in more detail Israel's use of military, spatial, economic and legal powers, as well as geopolitical maneuvering (particularly US support) to oppress Palestinians, while promoting democratic rights and economic development among Jews. Rivaling Palestinian political projects, including the refugees right of return, have been fragmented, ghettoized, attacked violently, and severely weakened. As a result, four major hierarchical types of citizenship have been created in Israel/Palestine, governed as 'separate and unequal' and mobility restrictions. The groups resemble the racialized categories used in Apartheid South Africa and include (a) 'White' – Jewish Israelis with full citizenship rights; (b) 'Colored' – Palestinian Arabs with Israeli citizenship with partial rights; (c) 'Black' – Palestinians under occupation lacking citizenship or political rights; (d) 'Gray' – an emerging group, consisting of non-citizen labor migrants and asylum seekers.